Getting rid of electrical and electronic equipment: Disposal decision and service life in the light of institutional economics - Bretschneider, Wolfgang (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Within the product life cycle, the user’s decision regarding disposal (i.e. getting rid of the product) at the end of the utilization phase plays an important role in terms of the service life of a device of electrical and electronic equipment (EEE). This article first examines from an economic perspective whether and how consumers dispose of EEE. The costs of ownership, the utility of ownership, and disposal costs are identified as the key determinants for this decision. It is the costs of ownership that is the actual cause of the will to dispose, and it is the latter two determinants that prevent the user from disposing of them. While the size of the utility of ownership is already frequently analyzed in the discourse on repair, the perspective of disposal costs seems to receive little attention. Therefore, the article continues to investigate the extent to which the determinant of disposal costs can be put to use for regulation towards a circular economy. To this end, three disposal paths (circular, official-final, illegal), the regulatory objectives associated with them (prevention, safe disposal) and the types of hurdles associated with the respective disposal path (pecuniary, transaction costs, spatial, sanctional) are considered. The result is a complex situation for regulation, not least because of a path of illegal disposal that is not easy to control, which makes it difficult to simply apply economic pricing instruments. Instead, the concept of ‘hurdle management’ is introduced, which offers a perspective for future regulatory efforts with regard to disposal costs.